EVALUASI KESESUAIAN PEDESTRIAN WAYS TERHADAP STANDAR TATA RUANG PERKOTAAN - Azhar Hasna Rany; Suci Aini Suryaning Pertiwi; Revi Aulia Purbandini (Vastutara : Arsitektur, Digital, Sejarah, Struktur dan Lingkungan, 2025)
This study aims to evaluate the compliance level of pedestrian ways in front of Goeteng Regional General Hospital (RSUD Goeteng) in Purbalingga with architectural and urban spatial planning standards. The area has undergone significant land-use conversion, where pedestrian spaces have been transformed into informal economic zones occupied by street vendors with semi-permanent structures. This situation creates spatial conflicts between public circulation functions and commercial activities, reducing safety and comfort for users, particularly vulnerable groups such as patients, the elderly, and persons with disabilities. The research employed a descriptive qualitative approach using measurable observation, behavioral mapping, and comparative analysis between the existing conditions and relevant regulations, including Pedestrian Comfort Theory, Technical Standards for Sidewalks Ministerial Regulation of Public Works No. 03/PRT/M/2014, and the Principles of Spatial Utilization Control Law No. 26/2007. The results indicate that the conversion of pedestrian paths into vending areas has reduced the free pedestrian zone width by up to 70%, obstructed accessibility for persons with disabilities, and decreased the Level of Service (LOS) for pedestrians to category F. This reflects a violation of public space functions and ineffective spatial utilization control. The study recommends implementing a human-centered and inclusive design approach for pedestrian ways that integrates social and economic activities while maintaining safety, accessibility, and sustainability in urban environments.